IMPLEMENTASI INTERNET OF THINGS DALAM KEHIDUPAN SEHARI-HARI - Fredy Susanto; Ni Komang Prasiani; Putu Darmawan (Jurnal Imagine, 2022)
ABSTRACT Internet of Things or abbreviated as IoT is a technology that innovates surrounding objects with the internet so that daily activities become easier and more efficient. The Internet of Things is a technology that allows objects around us to be connected to the Internet. The importance of the Internet of Things can be seen with the increasing number of applications in various lines of life today. IoT gives us many ideas to participate in various aspects of development ranging from micro to macro around the world. The internet of things has made it a separate field of research since the development of internet technology (IT) and other communication media. The methodology used in the development of IoT is of various kinds. From the real time system to the use of the prototype flow. The more human needs about technology are developing, the more research will be present, the internet of things is one of the thoughts of researchers who optimize several tools such as sensor media, Radio Frequency Identification (RFID), Wireless Sensor Networks and other Smart Objects that allow humans easy to interact with all equipment connected to the internet network. Keywords: IoT, RFID, Wireless Sensor Network, Smart Object ABSTRAK Internet of Things atau disingkat dengan istilah IoT merupakan teknologi yang menginovasi benda-benda sekitar dengan internet agar aktivitas sehari-hari menjadi lebih mudah dan efisien. Internet of Things adalah teknologi yang memungkinkan benda-benda di sekitar kita terhubung dengan Internet. Pentingnya Internet of Things dapat dilihat dengan semakin banyaknya diterapkan dalam berbagai lini kehidupan saat ini. IoT memberikan kita banyak gagasan untuk turut berperan serta dalam berbagai segi perkembangan mulai dari hal mikro hingga makro di seluruh dunia. Internet of things menjadikannya sebuah bidang penelitian tersendiri sejak berkembangnya teknologi internet (IT) dan media komunikasi lain. Metodology yang yang digunakan dalam pengembangan IoT ini adalah berbagai macam. Dari yang real time system hingga penggunaan alur prototype. Semakin berkembang keperluan manusia tentang teknologi, maka semakin banyak penelitian yang akan hadir, internet of things adalah salah satu hasil pemikiran para peneliti yang mengoptimasi beberapa alat seperti media sensor, Radio Frequency Identification (RFID), Wireless Sensor Network serta Smart Object lain yang memungkinkan manusia mudah berinteraksi dengan semua peralatan yang terhubung dengan jaringan internet. Kata kunci : IoT, RFID, Wireless Sensor Network, Smart Object